Effect of Dietary Addition of Fennel (Foeniculum vulgare) Seed on Growth Performance, Haemato-Biochemical Profile and Faecal Microbiota of Kankrej Calves - Pawar, M. M.; Patil, S. S.; Gami, Y. M.; Patel, S. S.; Raval, S. H.; Modi, C. P.; Patel, J. R. (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during the month of February and March, 2023 at Livestock Research Station, Kamdhenu University, Sardarkrushinagar, Gujarat, India to evaluate the effect of dietary addition of fennel (Foeniculum vulgare) seed on growth performance, haemato-biochemical profile and faecal microbiota of Kankrej calves. Eighteen Kankrej calves were randomly divided into three treatment groups, viz. Basal diet (control), Basal diet+5 g animal-1 day-1 of fennel seed powder supplementation and Basal diet+10 g animal-1 day-1 of fennel seed powder supplementation for a period of 60 days. Results revealed that there was numerically higher body weight gains were observed in groups fed 5 and 10 g of fennel seed daily than the control, the difference was statistically not significant (p>0.05) among the treatment groups. The mean faecal counts (log10 cfu g-1 in fresh faeces) of lactobacillus were increased, while coliform were reduced in groups fed 5 and 10 g of fennel seed daily as compared to control group. There was no effect (p>0.05) on the haemoglobin, haematocrit, total erythrocytes count and total leucocytes count among the treatment groups. No difference (p>0.05) was found in serum levels of total proteins, albumin, globulin, urea, triglycerides, cholesterol, ALT and AST concentrations among the treatment groups. It may be concluded that dietary fennel seed powder supplementation in calves improved growth performance and had beneficial effect on faecal microbiota with higher faecal lactobacillus count and lower faecal coliform count. Fennel seed supplementation did not affect haemato-biochemical profile of calves.